Pengaruh Solvabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di ISSI Tahun 2020-2024 - Yulia Rahmadani; Usdeldi Usdeldi (Lembaga Yasin AlSys, 2026)
Research on the factors influencing the financial performance of manufacturing firms continues to develop; however, studies that specifically examine the role of solvency, liquidity, and firm size in the sharia-based food and beverage sector remain limited. This study aimed to analyze the effect of solvency, liquidity, and firm size on the financial performance of manufacturing companies in the food and beverage sector listed on the Indonesia Sharia Stock Index (ISSI) during the 2020–2024 period. This research employed a quantitative approach with an explanatory research design, using a sample of 16 companies selected through purposive sampling. The research data consisted of annual financial reports obtained from the official website of the Indonesia Stock Exchange and were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis with the assistance of EViews version 12 software. The results showed that, partially, solvency and firm size did not have a significant effect on financial performance, whereas liquidity had a significant effect on financial performance. Simultaneously, solvency, liquidity, and firm size had a significant effect on financial performance. These findings confirm that a company’s ability to meet its short-term obligations plays an important role in improving financial performance, while the magnitude of assets and funding structure does not necessarily have a direct impact without efficient management. This study provides empirical contributions to the development of sharia finance literature and may serve as a reference for corporate management and investors in making financial decisions.